Embedded Linux system design and development - Raghavan, P. (Pichai), 1973- (Auerbach Publications, 2006)
Contains an embedded Linux system development roadmap for systems architects and software programmers. Explaining the issues that arise out of the use of Linux in embedded systems, this book facilitates movement to embedded Linux from traditional real-time operating systems, and describes the system design model containing embedded Linux.